2019
DOI: 10.1002/ana.25507
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic reactivity as predictor of neurological outcome in postanoxic coma: A multicenter prospective cohort study

Abstract: Objective Outcome prediction in patients after cardiac arrest (CA) is challenging. Electroencephalographic reactivity (EEG‐R) might be a reliable predictor. We aimed to determine the prognostic value of EEG‐R using a standardized assessment. Methods In a prospective cohort study, a strictly defined EEG‐R assessment protocol was executed twice per day in adult patients after CA. EEG‐R was classified as present or absent by 3 EEG readers, blinded to patient characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 38 publications
(149 reference statements)
0
57
1
4
Order By: Relevance
“…Target temperature varied across studies (ESM Table E3). Fifteen studies [ 22 36 ] were included for clinical examination, 12 for biomarkers [ 37 48 ], 26 for electrophysiology [ 49 74 ], and 15 for imaging [ 75 89 ], while 26 studies [ 90 115 ] were included for more than one prognostic modality. In all but four studies [ 43 , 88 , 99 , 104 ], poor outcome was reported as CPC 3–5.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Target temperature varied across studies (ESM Table E3). Fifteen studies [ 22 36 ] were included for clinical examination, 12 for biomarkers [ 37 48 ], 26 for electrophysiology [ 49 74 ], and 15 for imaging [ 75 89 ], while 26 studies [ 90 115 ] were included for more than one prognostic modality. In all but four studies [ 43 , 88 , 99 , 104 ], poor outcome was reported as CPC 3–5.…”
Section: Resultsmentioning
confidence: 99%
“…Sensitivity ranged from 23.1 to 40.5% ( Table 6). Absence of PLR in combination with the absence of CR on admission to hospital [28] or within 72 h [90] predicted poor neurological outcome with FPR ranging from 0 to 9.3% and sensitivity ranging from 27.1 to 28.4% ( Table 7). The absence of other brainstem reflexes, such as oculocephalic, gag, and cough, had 0% FPR starting from 48 h after ROSC.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations